2004
DOI: 10.1002/hyp.1472
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical variations during flood pulses in the south‐west China peak cluster karst: impacts of CaCO3–H2O–CO2interactions

Abstract: Abstract:High-resolution measurements of rainfall, water level, pH, conductivity, temperature and carbonate chemistry parameters of groundwater at two adjacent locations within the peak cluster karst of the Guilin Karst Experimental Site in Guangxi Province, China, were made with different types of multiparameter sonde. The data were stored using data loggers recording with 2 min or 15 min resolution. Waters from a large, perennial spring represent the exit for the aquifer's conduit flow, and a nearby well mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…In general, lower pH, EC, HCO 3 À concentrations and d 13 C DIC result from the high rainfall and water temperatures of the rainy season, and vice versa during the dry season. During the rainy season, fresh inflows of precipitation at low pH dilutes the karst water and dissolves further soil CO 2 to it (Liu et al, 2004(Liu et al, , 2007. The higher temperatures in the rainy season lead to increased biomass productivity, strong root respiration and organic decomposition, providing more soil CO 2 with low d 13 C (Atkin et al, 2000).…”
Section: Seasonal Variations Of Hydrochemistry and D 13 C Dic In The mentioning
confidence: 97%
See 2 more Smart Citations
“…In general, lower pH, EC, HCO 3 À concentrations and d 13 C DIC result from the high rainfall and water temperatures of the rainy season, and vice versa during the dry season. During the rainy season, fresh inflows of precipitation at low pH dilutes the karst water and dissolves further soil CO 2 to it (Liu et al, 2004(Liu et al, , 2007. The higher temperatures in the rainy season lead to increased biomass productivity, strong root respiration and organic decomposition, providing more soil CO 2 with low d 13 C (Atkin et al, 2000).…”
Section: Seasonal Variations Of Hydrochemistry and D 13 C Dic In The mentioning
confidence: 97%
“…CO 2 partial pressure (pCO 2 ) and the calcite saturation index (SI c ) are calculated from a geochemical model with pH, temperature and concentrations of seven major ions (Liu et al, 2004(Liu et al, , 2007Zhao et al, 2010). Since the host rocks in the regions are limestone and dolomite, intercalated with gypsum strata, Ca 2+ , Mg 2+ , HCO 3 À and SO 4 2À are the major ions.…”
Section: Calculating Co 2 Partial Pressure and The Calcite Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Determining partial pressure of CO 2 and calcite saturation within these waters (Neal et al, 2002;Liu et al, 2004); (2) Assessing the balance between photosynthesis and respiration by biota and CO 2 transfers at the airwater interface (Maberly, 1996); (3) Assessing the biological influences on CO 2 fluctuations in the water with respect to the precipitation/dissolution of calcite (Guasch et al, 1998;Liu et al, 2006); (4) Understanding geochemical processes in karst aquifers and characterizing carbonate aquifers (Shuster and White, 1971;Andreo et al, 2002); (5) Assessing karst-related carbon sink from atmosphere (Liu and Zhao, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed low variability in time also suggests that the typical approach of constant input chemistry is a reasonable approximation in many cases. Though a few site-specific studies have examined controls on carbonate system dynamics using time series data [e.g., Liu et al, 2004;Groves and Meiman, 2005;Pu et al, 2014], more work is needed to fully understand what determines whether dilution or CO 2 is important in a given setting or under given conditions. Prior work has shown that dilution is an important control on dissolution where runoff from noncarbonate rocks, which is undersaturated, mixes with or displaces groundwater from carbonate aquifers, which is saturated [Gulley et al, 2013[Gulley et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%